Illiterate Mother is a determinant of aggression - Hassan, Tuka Younis (Journal of the Faculty of Medicine Baghdad, 2020)
Most young children provoke negative reactions from parentral interference. These reactions worsen child's behavior. Starting a harmful pattern leading to emergence of an aggressive behavior. A cross sectional study was carried out in Al-Sadr city, Baghdad.  The target population was represented by all students attending governmental secondary schools, who are resident in Al-Sadr city aged between 13 and 21 year. The data collected by self-reported questionnaire (Aggression—Problem Behavior Frequency Scale). A total of 720 students contributed in this study. Out of the total, there were 257 (35.7%) students raised by illiterate mothers. Out of those, there were 241 (93.8%) students reported aggressive behavior.